Development of Non-viral Vectors for Delivery of CRISPR/Cas9 to Treat Inherited Retinal Diseases - Yanez, Vanessa. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Cell, Molecular & Developmental Biology.; Advisor: Rajendra Kumar-Singh.; Committee: James Schwob, Dong Kong, and Sheldon Rowan.; Keyword: Molecular biology.